2020
DOI: 10.3390/molecules25071601
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Content of Phenolic Compounds and Biological Activity in Traditional Mexican Herbal Infusions with Different Drying Methods

Abstract: Mexican spices are used in the supplementation of the human diet and as medicinal herbs for the particularly high amounts of compounds capable of deactivating free radicals. In addition, these spices can have beneficial effects on chronic, no-transmissible diseases such as type II diabetes and hypertension arterial. The objective of this study is to determine the content of phenolic compounds on the antioxidant activity and inhibitory enzymes of α-amylase, α-glucosidase and angiotensin-converting enzyme in mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
2
20
1
Order By: Relevance
“…In our study, it was found that extracts of hyssop, peppermint, and anise hyssop showed the maximum α-amylase and α-glucosidase inhibitory activities. The effects of extracts from the plants of the Lamiaceae family have also been confirmed in previously published studies [32][33][34][35][36]. The antihyperglycemic effect of their extracts is associated primarily with the presence of flavonoids, hydroxycinnamic acids, as well as diterpenes (forskolin and marrubiin), and triterpenes (ursolic and oleanolic acids) [2].…”
Section: Discussionsupporting
confidence: 57%
“…In our study, it was found that extracts of hyssop, peppermint, and anise hyssop showed the maximum α-amylase and α-glucosidase inhibitory activities. The effects of extracts from the plants of the Lamiaceae family have also been confirmed in previously published studies [32][33][34][35][36]. The antihyperglycemic effect of their extracts is associated primarily with the presence of flavonoids, hydroxycinnamic acids, as well as diterpenes (forskolin and marrubiin), and triterpenes (ursolic and oleanolic acids) [2].…”
Section: Discussionsupporting
confidence: 57%
“…The FD samples were characterized by a higher amount of flavonoid glycosides and cannabinoids, which are mainly in the acid form, while the oven-dried samples had a major relative content of the corresponding flavonoids aglycones. As demonstrated by Jimenez-Garcia et al [ 37 ], freeze-drying seems to be a better drying method to preserve flavonoid compounds, especially in the form of glycosides, considering that they may lose the sugar and degrade to the corresponding aglycone if exposed to high temperatures (65 °C) for a prolonged length of time. The same susceptibility is reported for cannabinoids in the acid form, although the degradation normally occurs at a higher temperature than 65 °C.…”
Section: Resultsmentioning
confidence: 99%
“…In turn, the freeze-drying process yielded the highest levels of potentially bioavailable p -hydroxybenzoic acid and sinapic acid. Similarly, in studies on other herbs where three drying methods (conventional, microwave, and freeze-drying) were used, the best extraction results were observed in the case of microwave drying and freeze-drying of melissa and thyme, respectively [ 22 ]. Importantly, these results only apply to “chemical extracts” [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in studies on other herbs where three drying methods (conventional, microwave, and freeze-drying) were used, the best extraction results were observed in the case of microwave drying and freeze-drying of melissa and thyme, respectively [ 22 ]. Importantly, these results only apply to “chemical extracts” [ 22 ]. In the case of dried lovage leaves, the jasmonic acid elicitation caused an increase in all phenolic acids identified in the potentially available fractions of phenolic compounds ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%